2001
DOI: 10.1051/0004-6361:20011349
|View full text |Cite
|
Sign up to set email alerts
|

Orbital variability of the PSR J2051-0827 binary system

Abstract: Abstract.We have carried out high-precision timing measurements of the binary millisecond pulsar PSR J2051−0827 with the Effelsberg 100-m radio telescope of the Max-Planck-Institut für Radioastronomie and with the Lovell 76-m radio telescope at Jodrell Bank. The 6.5-yrs radio timing measurements have revealed a significant secular variation of the projected semi-major axis of the pulsar at a rate ofẋ ≡ d(a1 sin i)/dt = (−0.23 ± 0.03) × 10 −12 , which is probably caused by the Newtonian spin-orbit coupling in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…Such a large modulation (Δmag ∼ 3 mags) is in good agreement with what is observed for similar objects in the Galactic field (e.g., Stappers et al 1999Stappers et al , 2001Pallanca et al 2012). Second, despite the low significance of the detection, there are some hints that the light curve could be asymmetric (e.g., the decrease to minimum seems to be steeper than the increase to maximum), possibly due to an asynchronously rotating companion as in the case of PSR J2051−0827 (Doroshenko et al 2001;Stappers et al 2001).…”
Section: The Companion To Psr J1518 + 0204csupporting
confidence: 86%
“…Such a large modulation (Δmag ∼ 3 mags) is in good agreement with what is observed for similar objects in the Galactic field (e.g., Stappers et al 1999Stappers et al , 2001Pallanca et al 2012). Second, despite the low significance of the detection, there are some hints that the light curve could be asymmetric (e.g., the decrease to minimum seems to be steeper than the increase to maximum), possibly due to an asynchronously rotating companion as in the case of PSR J2051−0827 (Doroshenko et al 2001;Stappers et al 2001).…”
Section: The Companion To Psr J1518 + 0204csupporting
confidence: 86%
“…Several other low-mass X-ray binaries (LMXBs), comprising both neutron star and black hole accretors, are also observed to show a faster evolution than expected (see Section 6 for an in-depth discussion). There isa similar behavior in many (nonaccreting) binary radio millisecond pulsars with orbital parameters similar to those ofSAX J1808.4−3658, known as BWs,where the rotational power emitted in the form of wind and radiation by the pulsar is impinging and ablating the semi-degenerate 9 donor companion (Nice et al 2000;Doroshenko et al 2001;Lazaridis et al 2011;Shaifullah et al 2016). These systems have a companion star with a typical mass of 0.1 M e , and several (but not all) of them have orbital periods of about 1-3 hr.…”
Section: Introductionmentioning
confidence: 92%
“…Previous pulsar timing analyses of PSR J2051−0827 have shown that the orbital period, P b , and projected semimajor axis, x, undergo secular variations (Stappers et al 1998;Doroshenko et al 2001;Lazaridis et al 2011). These variations are possibly linked to the variations of the gravitational quadrupole moment of the companion and induced by variations of the mass quadrupole of the companion as its oblateness varies due to rotational effects (Lazaridis et al 2011).…”
Section: Introductionmentioning
confidence: 97%